Physical Inactivity - Do We Hit Rock Bottom? - Aneta Rostkowska; Sebastian Kupisiak; Malwina Draim; Natalia Pasierb; Barbara Rękas; Michalina Kosowska; Wiktoria Dzierzgowska (Quality in Sport)
Introduction and purpose